Marketing Strategy And Creative Product Innovation On Coffee Business Marketing Performance - Andi Alfianto Anugrah Ilahi; Mulyana Machmud; Hamida Hasan; Fahmi Faturrahman (Journal of Studies in Academic, Humanities, Research, and Innovation, 2026)
This study aims to describe the role of marketing strategies and creative product innovation in improving marketing performance in coffee businesses. The approach used was qualitative with descriptive methods. Data were collected through in-depth interviews, observation, and documentation with coffee business owners and managers in Parepare City. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results show that marketing strategies implemented by coffee business actors include the use of social media, improving service quality, and strengthening local brands as the main attraction for consumers. Meanwhile, creative product innovation is realized through the development of flavor variants, attractive packaging designs, and product presentations that emphasize cultural values ​​and regional characteristics. These two aspects support each other in improving marketing performance, as seen from the increase in the number of customers, consumer loyalty, and the positive image of coffee businesses in the local market. This study confirms that successful marketing performance depends not only on promotional strategies, but also on the ability of business actors to innovate creatively according to market needs and tastes. Thus, the integration of marketing strategies and creative product innovation is key to the sustainability and competitiveness of coffee businesses in the modern era.